Daya Antibakteri Ekstrak Minyak Atsiri Temulawak (Curcuma xanthorrhiza Roxb.) terhadap Pertumbuhan Streptococcus viridans - Salsabilla Milatul Mirza; Pujiana Endah Lestari; Raditya Nugroho (Fakultas Kedokteran Gigi Universitas Jember, 2023)
Streptococcus viridans is one of the microorganisms found in root canals. The infection caused by S. viridans can cause an inflammatory response that will cause damage to the root canal. Infections in the root canal can be treated with root canal treatment. In the disinfection stage, a sterilization material is needed, one of which is Cresophene. However, certain people have an allergy to cresophene. Therefore, it is necessary to develop new drug options. Development of natural ingredients for alternative root canal sterilization drugs for patients who are hypersensitive to cresophene and have antibacterial effects with minimal side effects, one of which is essential oil extract of Curcuma xanthorrhiza Roxb. Essential oil extract of C. xanthorrhiza Roxb contains xanthorrhizol, camphene and curcumin which are antibacterial compounds. This study aims to determine the antibacterial activity of temulawak essential oil extracts on the growth of S. viridans. Temulawak is extracted using the steam and air distillation method. Inhibition test was carried out using the disc diffusion method. The concentration of essential oil extract of C. xanthorrhiza Roxb used were 25%, 50%, 75%, and 100%. The research data were statictically analyzed using SPSS with the Kruskal Wallis test. The average inhibition zone diameters at concentration of 25%, 50%, 75% and 100% is 0 mm, 8,22 mm, 12,16 mm, and 16,1 mm. Data anaylisis using Kruskal Wallis showed a significance value of 0,00 (p<0,05), which means that it has a significant difference. Essential oil extract of C. xanthorrhiza Roxb has antibacterial activity against S. viridans.